Permission to Drill for Troops Other than Volunteer Forces, etc., § 17 of Title 7, Acts and Resolutions of the General Assembly of the State of Georgia (1885) - (:unkn) unknown (General Publisher, 1885)
Prohibited any body men other than the state volunteer forces, US troops, or police to associate themselves as a military company, or to drill or parade, without a license of the governor. The license may be revoked at any time. Violators fined not exceeding ten dollars, or by imprisonment not exceeding six months, or both at the discretion of the court.
--
Keywords: MILITIAS